SAE Technical Paper Series 2011
DOI: 10.4271/2011-01-0900
|View full text |Cite
|
Sign up to set email alerts
|

Engine Efficiency Improvements Enabled by Ethanol Fuel Blends in a GDi VVA Flex Fuel Engine

Abstract: Advances in engine technology including Gasoline Direct injection (GDi), Dual Independent Cam Phasing (DICP), advanced valvetrain and boosting have allowed the simultaneous reductions of fuel consumption and emissions with increased engine power density. The utilization of fuels containing ethanol provides additional improvements in power density and potential for lower emissions due to the high octane rating and evaporative cooling of ethanol in the fuel. In this paper results are presented from a flexible fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The engine used in this study has been specifically developed for high-efficiency operation with ethanol [15]. The engine is a modified four-cylinder 2.0 L GM direct-injection spark-ignition (DISI) engine with turbocharging, dual independent cam phasing, and a 2-step valve train that enables both early and late intake valve closing for unthrottled operation for most of the load range.…”
Section: Engine Specifications and Operating Conditionsmentioning
confidence: 99%
“…The engine used in this study has been specifically developed for high-efficiency operation with ethanol [15]. The engine is a modified four-cylinder 2.0 L GM direct-injection spark-ignition (DISI) engine with turbocharging, dual independent cam phasing, and a 2-step valve train that enables both early and late intake valve closing for unthrottled operation for most of the load range.…”
Section: Engine Specifications and Operating Conditionsmentioning
confidence: 99%
“…al. 11 . examined the use of ethanol in a deactivated engine It was found that valve deactivation could improve combustion stability and efficiency at low load for ethanol blends.…”
Section: Introductionmentioning
confidence: 99%
“…Gasoline direct injection (GDI) has been widely applied in the production SI engines at an increasing rate over the last two decades [11][12][13][14][15]. Unlike intake-manifold injection, GDI directly injects fuel into the air via an injector in the cylinder head.…”
Section: Gasoline Direct Injectionmentioning
confidence: 99%
“…The calculation of each factor is shown from 8-14 to 8-18. Pumping loss was determined by the pumping work normalized by the fuel energy(8)(9)(10)(11)(12)(13)(14). Calculation of other energy losses from factor 2 to factor 5 is shown between 8-15 and 8-18, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation